2021
DOI: 10.1021/acsbiomedchemau.1c00039
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Oncogene Promoters and Ribosomal RNA Biogenesis by G-Quadruplex Binding Ligands Translate to Anticancer Activity

Abstract: G-Quadruplex (GQ) nucleic acids are promising therapeutic targets in anticancer research due to their structural robustness, polymorphism, and gene-regulatory functions. Here, we presented the structure−activity relationship of carbazole-based monocyanine ligands using region-specific functionalization with benzothiazole (TCA and TCZ), lepidine (LCA and LCZ), and quinaldine (QCA and QCZ) acceptor moieties and evaluated their binding profiles with different oncogenic GQs. Their differential turnon fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Here, it may be noted that cyclic polymers have drawn much attention due to their exceptional properties like small hydrodynamic volume and lower intrinsic viscosity. , From the scientific and industrial points of view, carbazole-based polymers have attracted more attention due to their hole transport, high charge-carrier mobility, and electroluminescent properties. , Among carbazole polymers, pNVC is much more familiar due to its easy synthesis procedure and solubility in most organic solvents. , They are used as biosensors, cellular markers, protective agents against radiation, and antimicrobial coatings. ,, The non-toxic nature of pNVC was also tested against NIH 3T3 mammalian fibroblast cells. The results demonstrated that pNVC-based material was nontoxic to fibroblast cells, meaning that this material is appropriate for tissue engineering applications .…”
Section: Introductionmentioning
confidence: 99%
“…Here, it may be noted that cyclic polymers have drawn much attention due to their exceptional properties like small hydrodynamic volume and lower intrinsic viscosity. , From the scientific and industrial points of view, carbazole-based polymers have attracted more attention due to their hole transport, high charge-carrier mobility, and electroluminescent properties. , Among carbazole polymers, pNVC is much more familiar due to its easy synthesis procedure and solubility in most organic solvents. , They are used as biosensors, cellular markers, protective agents against radiation, and antimicrobial coatings. ,, The non-toxic nature of pNVC was also tested against NIH 3T3 mammalian fibroblast cells. The results demonstrated that pNVC-based material was nontoxic to fibroblast cells, meaning that this material is appropriate for tissue engineering applications .…”
Section: Introductionmentioning
confidence: 99%
“…31 A recent study also showed that several benzothiazole−carbazole hybrids had the potential to be selective c-MYC G-quadruplex ligands. 37 In view of these, we therefore employed carbazole to extend the aromatic system of benzoazoles. The other modification direction we took was to increase the binding of benzoazole to the groove and loop regions of the c-MYC G-quadruplex by introducing an appropriate side chain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Benzoazoles are a class of benzene-fused heterocyclic compounds including benzothiazole, benzoxazole, benzoselenazole, and so forth. Among them, the benzothiazole scaffold has been widely used in the design of fluorescent probes and medicinal agents for G-quadruplexes. However, compared to the extensive attention devoted to benzothiazole, there are relatively few studies on its analogues benzoxazole and benzoselenazole. Especially for benzoselenazole, there is considerable evidence that incorporating selenium into heterocycles may improve their pharmacological activities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Neither StyBtz nor StyTz have been tested as E ⇄ Z -photoisomerisable photopharmaceuticals, not even in cell-free assays. However, (1) StyBtz photochemistry has been studied: they E ⇄ Z -photoisomerise reversibly in organic and aqueous media, 27 and have fluorescence emission around 500 nm 28 (note the similarity of push–pull StyBtz to truncated Cy dyes); and (2) some E -StyBtz, though structurally distant, have been reported to have general antiproliferative activity against eukaryotic cells 29–32 (and further reports of E -StyBtz for cell-free or bacterial applications have also been made 33 ). Therefore, while applications to live-cell protein control in eukaryotes, based on in-cell photoswitchability, have remained untested until now, these were indications that suitable E ⇄ Z -photoisomerisable designs could be applicable.…”
Section: Introductionmentioning
confidence: 99%